Wong's nursing care of infants and children / Marilyn J. Hockenberry, Elizabeth A. Duffy, Karen DiValerio Gibbs. - Hockenberry, Marilyn J.; Duffy, Elizabeth A. (St. Louis, Missouri : Elsevier, 2024)
Provide quality nursing care through each stage of child development! Wong's Nursing Care of Infants and Children, 12th Edition uses an easy-to-follow, family-centered approach to describe the care of children at each age and stage of development. The book begins with a discussion of the influences on and assessment of child health, then provides chapters on child health promotion and health problems -- all organized by age groups and body systems. Up-to-date, evidence-based information helps you develop critical thinking skills along with the sensitivity needed to become a compassionate, caring pediatric nurse. Written by a team of experts led by Marilyn J. Hockenberry, Wong's continues to be the leading text in pediatric nursing.--Publisher's website.
Includes bibliographical references and index.
Keywords: Pediatric nursing -- Textbooks; Infants -- Care